The Influences of Medical Students' Consent to Participate in Thalassemia Research - Wratsangka, Raditya; Adriani, Donna; Tungka, Endrico Xavierees; Murthi, Aditya Krishna (Kesmas, 2024)
An effective way of learning about thalassemia, a complex public health issue with multiple perspectives, is through participating in research. This study used an inductive approach to presume the influencing factors of students' consent to participate in thalassemia research voluntarily. Nested in the preliminary stage of a research series on thalassemia, this study used a consecutive sampling to recruit 140 medical undergraduates. Their knowledge, experience, and attitude to thalassemia and the perception of self-quality life were assessed using self-administered questionnaires. Blood samples were drawn for carrier screening. Students' GPAs were collected from faculty records. Of 140 participants, only 123 had at least heard of thalassemia, and their data was used in the analysis. Most participants had fairly good but incomplete knowledge of inheritance patterns, antenatal screening, and thalassemia management. Premarital screening was known and received the most positive attitudes from participants. Inductively, academic performance and carrier status curiosity were presumed to influence students' consent to participate. With the limitation of an inductive approach, further study with a specific design is needed to closely investigate student perspectives on research and their drives to get involved.